(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article looks at how science and technology progress affects the world economy. It explains the stages of industrial revolutions, important inventions, and new technologies, and how they changed social and economic life. The study also shows the good sides of progress – higher production, more global trade, and better living standards – as well as the bad sides, such as unemployment, inequality, and environmental problems.